COVID-19 Vaccination: Concerns About Its Accessibility, Affordability, and Acceptability - Ali, Inayat; Ali, Shahbaz; Iqbal, Sehar (Frontiers in Medicine, 2021)
After an almost yearlong COVID-19 pandemic that has significantly affected the world in multiple ways, various vaccines against COVID-19 have arrived and started in some countries. Yet, economic, (geo)political, and socio-cultural factors may influence its uptake at individual and country levels. However, several issues will (and already have been reported in media) revolve around this vaccination regarding its accessibility, affordability, and acceptability at an individual level and a country level. Given that in this commentary, we provoke a discussion: Who—a country as well as the individuals—would have access to it, and who would economically afford it, and who would accept it? Centring these intriguing questions, we revisit the body of literature that explicates vaccine hesitancy, refusal, and resistance, and we also draw on the current literature and media reports about vaccination against COVID-19. We suggest that these backdrops need essential attention so that everyone can afford, accept, and have access to it. Otherwise, the current risk in the face of a year-old pandemic will continue.